Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Wyłącz wspólny czynnik przed nawias. a) 6x³-3x²+x 3.83 gwiazdek na podstawie 6 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Wyłącz wspólny czynnik przed nawias. a) 6x³-3x²+x

2.1.
 Zadanie
2.2.
 Zadanie

3
 Zadanie

1
 Zadanie
2
 Zadanie
3
 Zadanie

`a) \ \ 6x^3-3x^2+x=x*6x^2+x*(-3x)+x*1=x(6x^2-3x+1)` 

`b) \ \ 9x^3+3x^2-12x=3x*3x^2+3x*x+3x*(-4)=3x(3x^2+x-4)` 

`c) \ \ 10x-5y-15=5*2x+5*(-y)+5*(-3)=5(2x-y-3)` 

`d) \ \ 4x^4-8x^3+16x^2=4x^2*x^2+4x^2*(-2x)+4x^2*4=4x^2(x^2-2x+4)` 

`e) \ \ 12x^6+6x^5-6x^4=6x^4*2x^2+6x^4*x+6x^4*(-1)=6x^4(2x^2+x-1)` 

`f) \ \ 2x^2y-4xy^2-2x^2y^2=2xy*x+2xy*(-2y)+2xy*(-xy)=2xy(x-2y-xy)` 

`g) \ \ 3x^2y^2-9xy^2+15x^2y=3xy*xy+3xy*(-3y)+3xy*5x=3xy(xy-3y+5x)` 

`h) \ \ 2x^2y^2z-4xz^2+x^2yz=xz*2xy^2+xy*(-4z)+xz*xy=xz(2xy^2-4z+xy)` 

`i) \ \ 7x^2y^3+xy^2z+3x^2y^3z=xy^2*7xy+xy^2*z+xy^2*3xyz=xy^2(7xy+z+3xyz)`